Bibliography of the Septuagint = Bibliographie de la Septante : (1970-1993) - Dogniez, Cécile. (Supplements to Vetus Testamentum,, 1995)
Ce volume est Ia suite de S. P. Brock, C.T. Fritsch et S. Jellicoe, A Classified Bibliography of the Septuagint (Brill, Leiden 1973) pour les publications parues sur la Septante entre 1970 et 1993. Cette bibliographie regroupe d'abord les études sur le texte grec proprement dit- éditions, langue des traducteurs, techniques de traduction, critique textuelle, manuscrits de Ia Septante trouvés à Qumrân, réception dans le judaïsme hellénistique (Philon, Flavius Josèphe) et le christianisme ancien (Nouveau Testament et Pères). Viennent ensuite les études particulières, classées par livre biblique, suivies des études sur les versions, orientales et latines, issues de la Septante. Le volume s'achève sur les travaux consacrés aux illustrations de la Septante. Cet instrument de travail s'adresse à tous ceux qui s'intéressent à la Bible, au judaïsme et au christianisme de l'Antiquité. This volume is a successor to A Classified Bibliography of the Septuagint ( Brill , Leiden 1973), by S.P. Brock, C.T. Fritsch and S. Jellicoe, for the literature on the Septuagint published between 1970 and 1993. It includes general publications on the Greek text - editions, language, translators' techniques, textual criticism, Septuagint manuscripts from Qumran and the use of the Septuagint in Ancient Judaism (Philon, Josephus) and Christianity (New Testament and Patristica). Particular studies are then classified by the individual books of the Bible, followed by literature on Oriental and Latin versions derived from the Septuagint. The studies on the illustrations of the Septuagint are included at the end. This reference tool will be indispensable for scholars or students interested in Bible, Judaism and Christianity in Late Antiquity.